Validation of the factor structure of the Experiences Questionnaire using Exploratory Graph Analysis - Rader, Lena; Drueke, Barbara; Forster, Saskia Doreen; Gauggel, Siegfried; Mainz, Verena (Frontiers in Psychology, 2023)
Decentering describes the ability to shift the focus away from one's subjective experience onto the experience itself. The Experiences Questionnaire (EQ) is a self-report measure that was developed to systematically assess changes in Decentering ability. Although several studies show the validity of the questionnaire, there are discrepancies between the factorial structure of the Decentering scale of the EQ (EQ-D) found in the initial study (one factor) and other studies (two factors). Therefore, the current study aimed to assess the dimensionality of the EQ-D using Exploratory Graph Analysis (EGA). In total, 1100 participants were recruited online (790 female, 307 male, 3 non-binary; age 18 to 65 years). Participants completed the EQ and the Rosenberg Self-esteem scale (RSES). The bootstrapped EGA results revealed a two-dimensional structure of the EQ-D (Factor 1: Distanced Perspective, DP; Factor 2: Accepting Self-perception, AS) with high structural and item stability (all items > .70). The two dimensions of the EQ-D showed a high internal consistency (DP: ω = .74; AS: ω = .86) and discriminant validity with the rumination items of the EQ. Furthermore, a high convergent validity of the EQ was established, as the AS factor exhibited a significantly stronger correlation with self-esteem than the DP factor (z = 7.98, p < .001), which aligns with theoretical considerations suggesting that the AS factor encompasses aspects of self-compassion alongside decentering. We also found measurement invariance of the DP and AS factor across age, gender and country but not for education. These results support the EQ's validity, demonstrated in a larger sample with a new methodology, aligning with existing two-factor decentering models literature.